Support of Open Science in Technische Informationsbibliothek — TIB - Nazarovets, M. A. (Visnyk Kharkivsʹkoï derz͡h︡avnoï akademiï kulʹtury, 2022)
The relevance. Libraries in Europe are implementing services to support the information needs of researchers in the direction of the Open Science movement. Further integration of Ukrainian science into the European Research Area requires Ukrainian libraries to actively adopt the experience of colleagues. The purpose of the paper is to investigate and summarize the experience of the Leibniz Information Centre for Science and Technology and University Library (Technische Informationsbibliothek — TIB) in support of Open Science. The methodology. Methods of analytics, differentiation, and generalization in the process of processing information from official sources, research publications, and personal communication with employees of the institution were used. Conclusions. It was found that the ideas of Open Science are leading in the implementation of the tasks of the library, and the approach to their implementation is comprehensive: digitization of information; emphasis on digital technology; maximum access to scientific information; use of semantic search technologies; implementation of Open access publishing; conducting researches, introduction of new and improvement of common tools for the organization of library services in support of Open Science; communication and cooperation at national and international levels to share experiences and find optimal developments on the path to openness.